Network- and systems-based re-engineering of dendritic cells with non-coding RNAs for cancer immunotherapy - Lai, Xin; Dreyer, Florian; Cantone, Martina; Eberhardt, Martin; Gerer, Kerstin F.; Jaitly, Tanushree; Uebe, Steffen; Lischer, Christopher; Ekici, Arif Bülent; Wittmann, Jürgen; Jäck, Hans-Martin; Schaft, Niels; et al. (Theranostics, 2021)
Dendritic cells (DCs) are professional antigen-presenting cells that induce and regulate adaptive immunity by presenting antigens to T cells. Due to their coordinative role in adaptive immune responses, DCs have been used as cell-based therapeutic vaccination against cancer. The capacity of DCs to induce a therapeutic immune response can be enhanced by re-wiring of cellular signalling pathways with microRNAs (miRNAs). Methods: Since the activation and maturation of DCs is controlled by an interconnected signalling network, we deploy an approach that combines RNA sequencing data and systems biology methods to delineate miRNA-based strategies that enhance DC-elicited immune responses. Results: Through RNA sequencing of IKKβ-matured DCs that are currently being tested in a clinical trial on therapeutic anti-cancer vaccination, we identified 44 differentially expressed miRNAs. According to a network analysis, most of these miRNAs regulate targets that are linked to immune pathways, such as cytokine and interleukin signalling. We employed a network topology-oriented scoring model to rank the miRNAs, analysed their impact on immunogenic potency of DCs, and identified dozens of promising miRNA candidates, with miR-15a and miR-16 as the top ones. The results of our analysis are presented in a database that constitutes a tool to identify DC-relevant miRNA-gene interactions with therapeutic potential (www.synmirapy.net/dc-optimization). Conclusions: Our approach enables the systematic analysis and identification of functional miRNA-gene interactions that can be experimentally tested for improving DC immunogenic potenc
CRIS-Team WoS Importer:2020-12-11
Keywords: dendritic cell; therapeutic vaccination in cancer; systems biology; network biology; microRNAs: bioinformatics